(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the stages of creativity, independent learning, and the use of interesting and historical information and modern educational methods in the formation of pedagogical compensations for future chemistry teachers, as well as the organization of non-traditional chemistry lessons and increasing students’ interest in teaching chemistry, improving the methodology, its structural structure and content, and introducing it into educational practice. Also, the level of mastery of skills and competencies in designing lesson plans based on a creative approach among future chemistry teachers, and similar information is provided.